Flow Injection Analysis and Spectrophotometric Determination of Nifedipine in Pharmaceutical Formulation - السعيدي، انتصار مظفر; عبد، سديم صبحي (جامعة بغداد - مركز بحوث السوق وحماية المستهلك, 2019)
تم وصف طريقة طيفية جديدة بسيطة وحساسة للتقدير الكمي للنفديبين ومستحضره الصيدلاني، حيث أنجزت من خلال اختزال مجموعة النايترو للنفديبين لتتحول إلى مجموعة أمينو أولية بتفاعله مع مسحوق الخارصين وحامض الهيدروكلوريك المركز، تم تفاعل الناتج مع كاشف البايروكاتيكول ونترات ثنائي أمونيوم سيريوم الرباعي عن طريق تفاعل الازدواج التأكسدي، مما نتج عنه محلول ذو لون برتقالي تم قياسه طيفيا عند طول موجي 467 نانومتر وقد استعملت منظومة الحقن الجرياني لإجراء التقدير كما تم اختيار الظروف المثلى الكيميائية والفيزيائية، كان منحني المعايرة ضمن مدى 5.0 إلى 140.0 ميكروغرام/ مل مع حد الكشف والقياس الكمي 1.48 و 4.96 ميكروغرام/ مل على التوالي، وتم الحصول على دقة جيدة ونقاط تشتت منخفضة في الرسم البياني لمنحني المعايرة وضبط جيد كذلك قدمت تقنية التحليل بالحقن الجرياني مدى خطي جيد مع حساسية مقبولة، معامل الارتباط كان عاليا (0.9996)، أن الطريقة المقترحة استعملت بشكل ناجح في فحص وتقدير النفديبين وكذلك مستحضره الدوائي.
A new simple and sensitive spectrophotometric method is described for quantification of Nifedipine (NIF) and their pharmaceutical formulation. The selective method was performed by the reduction of NIF nitro group to yield primary amino group using zinc powder with hydrochloric acid. The produced aromatic amine was submitted to oxidative coupling reaction with pyro catechol and ammonium ceric nitrate to form orange color product measured spectrophotometric ally with maximum absorption at 467nm. The product was determined through flow injection analysis (FIA) system and all the chemical and physical parameters were optimized. The concentration range from 5.0 to 140.0 μg. mL-1 was obeyed Beer’s law with a limit of detection and quantitation 1.48 and 4.96 μg. mL-1 respectively. Agood precision, low scattering point of the calibration graph and good accuracy in addition, FIA introduced a good linear range with acceptable sensitivity. High correlation coefficient (0.9996) was found. The proposed method was successfully applied to assay NIF and its pharmaceutical dosage also could be utilized for pharmaceutical routine analysis of the drug.
Keywords: المستحضرات الصيدلانية -- النفديبين -- المقياس الطيفي -- الحقن الجرياني -- تفاعل الازدواج التأكسدي